2014
DOI: 10.31018/jans.v6i1.367
|View full text |Cite
|
Sign up to set email alerts
|

A study on few biochemical parameters of clinically suspected and laboratory confirmed Leptospirosis cases

Abstract: Abstract:A study on biochemical parameters in clinically suspected and laboratory-confirmed leptospirosis cases was conducted in the Union Territory of Dadra and Nagar Haveli. Out of 50 clinically suspected samples of leptospirosis, 38% were positive from both ELISA IgM and rapid card test. In the present study, liver markers such as bilirubin, Serum Glutamate Oxalo acetic Transaminase (SGOT) and Serum Glutamate Pyruvic Transaminase (SGPT) encountered elevation 68%, 100% and 89% respectively in leptospiosis po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The elevated SGOT and SGPT were encountered 100%, 89% in study by D. B. Zala, Vikram Khan and V. K. Das et al 10 The association between level of elevated SGOT, SGPT, total bilirubin, direct bilirubin and ALP at admission between survived patients and death patients among study subjects were found to be significant. This showed that those patients who died had raised levels of transaminase and bilirubin than those who survived.…”
Section: Discussionmentioning
confidence: 96%
“…The elevated SGOT and SGPT were encountered 100%, 89% in study by D. B. Zala, Vikram Khan and V. K. Das et al 10 The association between level of elevated SGOT, SGPT, total bilirubin, direct bilirubin and ALP at admission between survived patients and death patients among study subjects were found to be significant. This showed that those patients who died had raised levels of transaminase and bilirubin than those who survived.…”
Section: Discussionmentioning
confidence: 96%
“…Nearly 160 mammalian species are the reservoirs and sources of infection, such as rodents, cattle, pigs, buffaloes, horses, sheep, goats, squirrels, bandicoots, and raccoons. (Zala et al 2014). This disease is caused by different serogroups that belong to the species Leptospira interrogans .…”
Section: Introductionmentioning
confidence: 98%
“…Leptospirosis is one of the six diseases enlisted by OIE with reference to "animal diseases and climate change" (19). The disease is most commonly found in rural and urban areas of tropical and subtropical parts of the world (30). It spreads more readily in tropical regions as Leptospira can survive longer in warm and humid environment.…”
Section: Introductionmentioning
confidence: 99%